proposed method for solving interval valued linear fractional programming problem (Journal of Hama University, 2024)
This research paper presents a proposed method for solving the interval-valued linear fractional programming problem IVLFP, which takes into consideration change and instability in the data that reaches the decision maker.The IVLFP problem that we have studied contains interval valued coefficients in the objective function and the right side of constraints: It turns out that the proposed method is feasible and capable of solving interval valued linear fractional programming problem effectively.
Keywords: linear fractional programming; , interval valued linear fractional programming; simplex method